Large-scale IPM validation in Basmati rice (Oryza sativa) in Western Uttar Pradesh, India - TANWAR, R K; SINGH, S P; SHARMA, O P; KANWAR, V; MUKHERJEE, IRANI; CHATTOPADHYAY, C (The Indian Journal of Agricultural Sciences, 2016)
Pusa Basmati 1121, a high-yielding aromatic rice (Oryza sativa L.) variety released by ICAR-IARI in 2005, became widely popular among farmers of Punjab, Western Uttar Pradesh and Haryana in India due to higher yield and good price in the market. But, soon after its release, the variety was severely affected by bakanae foot rot disease (Fusarium fujikuroi). The ICAR-National Research Centre for Integrated Pest Management (NCIPM) synthesized an integrated pest management (IPM) module and validated it in large-scale at Bambawad village (District Gautam Budh Nagar, UP) in farmers’ participatory mode during 2010-14. The trial was initiated on 40 ha in 2010, which was gradually increased to 80, 120, 200 and 286 ha during 2011, 2012, 2013 and 2014, respectively. The IPM module involved green manuring, seed treatment with carbendazim, seedling root dipping in Pseudomonas fluorescens, pest monitoring and need-based application of bioagents/ pesticides. Implementation of the module resulted in a significant reduction in the incidence of bakanae ranging from 0.05±0.01 to 10.18±4.05% in IPM fields against 1.22±0.27 to 46.5±6.30% in Farmers’ practices (FP). Brown plant hopper (Nilaparvata lugens) population (average of the season) remained 7.74, 9.55, 1.22, 4.32 and 0.49 nymphs and adults/hill in IPM against 31.13, 14.16, 1.36, 7.24 and 0.82 in FP fields during 2010, 2011, 2012, 2013 and 2014, respectively. Regular pest monitoring and ETL-based application of pesticides in IPM helped in conservation of spider population in IPM as compared to FP with very low application of chemical pesticides, i.e. 103.2 g a.i./ha in IPM against 1214.4 g a.i./ha in FP. Analysis of rice grain samples for pesticide residue indicated carbendazim below detectable level. IPM trial also resulted in higher yield (36.01 q/ha in IPM against 26.24 q/ha in FP) and benefit- cost ratio (3.80 in IPM and 2.56 in FP) as compared to FP (Average of five years).